Estimation of Location and Extent of Labral Tear Based on Preoperative Range of Motion in Patients Undergoing Arthroscopic Stabilization for Anterior Shoulder Instability - Darby A. Houck, B.A; Robin H. Dunn, M.D; Carolyn M. Hettrich, M.D., M.P.H; Brian R. Wolf, M.D., M.S; Rachel M. Frank, M.D; Eric C. McCarty, M.D; Jonathan T. Bravman, M.D; Matthew J. Bollier, M.D; John E. Kuhn, M.D., M.S; Charles L. Cox, M.D., M.P.H; C. Benjamin Ma, M.D; Brian T. Feeley, M.D; et al. (Elsevier, 2020)
Purpose: To determine whether range of motion (ROM) varies with the location and extent of labral tear seen in patients undergoing arthroscopic anterior shoulder stabilization. Methods: Consecutive patients undergoing arthroscopic anterior shoulder stabilization who were enrolled in the Multicenter Orthopaedic Outcomes Network Shoulder Instability database underwent a preoperative physical examination and intraoperative examination under anesthesia in which ROM was recorded. Intraoperatively, the location and extent of the labral tear was recorded using conventional clock-face coordinates. Patients were grouped by combinations of quadrants involved in the labral tear (G1-G7): G1 = anterior only, G2 = anterior + inferior, G3 = anterior + inferior + posterior, G4 = all quadrants, G5 = superior + anterior, G6 = superior + anterior + inferior, and G7 = posterior + superior + anterior. Statistical analyses were performed with the Kruskal-Wallis rank-sum test. When P < .05, a post-hoc Dunn's test was performed. For categorical variables, the χ2 test was performed. We performed a series of bivariate negative binomial regression models testing pairwise combinations of ROM parameters predicting the count of labral tear locations (possible: 0-5) within each quadrant. Results: A total of 467 patients were included, with 13 (2.8%) in G1, 221 (47.3%) in G2, 40 (8.6%) in G3, 51 (10.9%) in G4, 18 (3.9%) in G5, 121 (25.9%) in G6, and 3 (0.6%) in G7. Multiple statistically significant differences were noted in ROM, specifically active internal rotation at side (IRS) (P = .005), active abduction (P = .02), passive IRS (P = .02), and passive external rotation in abduction (P = .0007). Regression modeling revealed a positive correlation between passive abduction and predicted count of labral tear locations in the superior quadrant and between passive IRS and predicted count of labral tear location in the inferior quadrant. Conclusions: In patients undergoing arthroscopic shoulder stabilization for anterior instability, ROM varies with location and extent of labral tear. However, the clinical relevance of such small ROM differences remains undetermined. Level of evidence: II, prospective comparative study.